How art becomes organization: Reimagining aesthetics, sites and politics of entrepreneurship. Issue 2 (February 2022) - Holm, Ditte Vilstrup; Beyes, Timon
Art and entrepreneurship both demonstrate a particular power to experiment with how the social is apprehended, organized and inhabited. How can we then understand and theorize the particular power of art understood as entrepreneurial organizing? In this paper, we develop the concept of artistic entrepreneuring. It is based on contemporary art's wide-ranging 'organizational turn', where art becomes organization by experimenting with forms and processes of emancipatory organizing. Interweaving art theory, examples of art's organizational turn and a processual understanding of public entrepreneurship, we conceptualize artistic entrepreneuring as fundamentally aesthetic, necessarily sited and invariably political, and we discuss the implications for entrepreneurship studies and research on the aesthetics and politics of organizing.